Clinical Impact of Corrections to Infliximab and Adalimumab Monitoring Results with the Homogeneous Mobility Shift Assay - Papamichael, Konstantinos (J Clin Med, 2020)
An upward drift for both infliximab and adalimumab concentrations measured by the homogenous mobility shift assay (HMSA) was previously reported. We aimed to investigate the impact of this drift on clinical care of patients with inflammatory bowel disease. This was a retrospective, multicenter study. Providers reviewed the individual patient data and drug concentrations before and after the laboratory corrections and then documented whether a different clinical decision would have been made had the corrected drug concentration been originally reported. A multivariable Cox proportional hazards regression analysis was performed to investigate the association of a documented treatment change with treatment failure, defined as drug discontinuation for primary nonresponse, loss of response, or serious adverse event, adjusting for confounding factors. The study population consisted of 479 patients (infliximab, n = 219; adalimumab, n = 260). Upon review, 14.9% (71/479) patients would have had a different treatment decision made had the corrected drug concentration been initially reported. After a median follow-up of 10.6 months, 25.7% of patients (123/479) had treatment failure. A theoretical different clinical decision based on the corrected drug concentrations was not associated with treatment failure (adjusted hazard ratio (HR): 1.452; 95% confidence interval (CI): 0.805–2.618; p = 0.216), which was consistent for both infliximab (adjusted HR: 1.977; 95% CI: 0.695–5.627; p = 0.201) and adalimumab (adjusted HR: 1.484; 95% CI: 0.721–3.054; p = 0.284). The drift in infliximab and adalimumab concentrations in the HMSA assay affected treatment decisions in 15% of cases. However, this discrepancy was not associated with a higher cumulative probability for treatment failure.